Untangling the Contributions of Sex-Specific Gene Regulation and X-Chromosome Dosage to Sex-Biased Gene Expression in Caenorhabditis elegans. Issue 1 (1st September 2016) - Kramer, Maxwell; Rao, Prashant; Ercan, Sevinc
Abstract: Dosage compensation mechanisms equalize the level of X chromosome expression between sexes. Yet the X chromosome is often enriched for genes exhibiting sex-biased, i.e., imbalanced expression. The relationship between X chromosome dosage compensation and sex-biased gene expression remains largely unexplored. Most studies determine sex-biased gene expression without distinguishing between contributions from X chromosome copy number (dose) and the animal's sex. Here, we uncoupled X chromosome dose from sex-specific gene regulation in Caenorhabditis elegans to determine the effect of each on X expression. In early embryogenesis, when dosage compensation is not yet fully active, X chromosome dose drives the hermaphrodite-biased expression of many X-linked genes, including several genes that were shown to be responsible for hermaphrodite fate. A similar effect is seen in the C. elegans germline, where X chromosome dose contributes to higher hermaphrodite X expression, suggesting that lack of dosage compensation in the germline may have a role in supporting higher expression of X chromosomal genes with female-biased functions in the gonad. In the soma, dosage compensation effectively balances X expression between the sexes. As a result, somatic sex-biased expression is almost entirely due to sex-specific gene regulation. These results suggest that lack of dosage compensation in different tissues and developmental stages allow X chromosome copy number to contribute to sex-biased gene expression and function.